DIFFERENCES IN MENTAL POTENTIAL OF YOUNG FEMALE ATHLETES - Branko Đukić,; Snežana Vujanović,; Branislav Strajnić,; Vladimir Ivanek, (Sport Scientific And Practical Aspects, 2025)
Success in a particular sports branch is determined by a large number of factors, abilities and characteristics that are necessary for players to respond to specific requirements and the structure of a different sport. Knowing the hierarchy of anthropological characteristics and abilities dominant for a particular sporting branch, should serve to sports professionals as the starting point in the management of the training process. Each athletic competition at the same time is both physical and technical-tactical, and also mental. The importance of psychic factors has its confirmation in every competition (Lazarević, 2003). Many sports branches require developed visual motor coordination and reaction speed. The aim of this paper is to determine similarities or differences in mental potential with the following abilities: psychomotor speed and movements coordination between young table-tennis, karate and volleyball female players. Multivariate variance analysis (MANOVA) has shown that there are differences in the expression of cognitive abilities among girls involved in various sports in the whole system of observed variables (p = ,00)